De l’instrument joué à la pratique représentée : comprendre les figures de flûtistes dans l’iconographie recuay (sierra nord-centrale du Pérou, 100‑800 n.è.) - Mélanie Ferras; Alexia Moretti (Frontière·s)
The analysis of musical and sound practices of the Recuay culture (100‑700 CE), in the north-central highlands of actual Peru, encounters several documentary unknowns. Indeed, there is an unbalanced distribution of exploitable data. The archaeological contexts and instruments, which are poorly known and scarcely documented, contrast with a rich imagery found on ceremonial ceramics that depict detailed and recurring scenes involving musical instruments.The representation of flutists on ceramics is particularly intriguing. The figure of the instrumentalist is consistently central, and his attributes connect him to the priestly domain. However, it would be reductive to merely state that the use of the flute’s sound is associated with a ceremony. Formal and symbolic analyses of the depicted motifs reveal, on a single piece, the juxtaposition of distinct levels of reality that come into contact through the presence of the flute.In the presented case, the iconographic approach provides the opportunity to scientifically ‘revive’ decontextualized objects. In doing so, it highlights information conveyed by the images that reflect the worldview of a culture.